B-cell depletion reveals a role for antibodies in the control of chronic HIV-1 infection - Huang, K; Bonsall, D; Katzourakis, A; Thomson, E; Fidler, S; Main, J; Muir, D; Weber, J; Frater, A; Phillips, R; Pybus, O; Goulder, P; et al. (Springer Nature, 2010)
HIV can be partially contained by host immunity and understanding the basis of this may inform vaccine design. The importance of B-cell function in long-term control is poorly understood. One method of investigating this is in vivo cellular depletion. In this study, we take advantage of a unique opportunity to investigate the role of B cells in an HIV-infected patient. The HIV-1+ patient studied here was not taking antiretroviral drugs and was treated for pre-existing low-grade lymphoplasmacytoid lymphoma by depletion of CD20+ B cells using rituximab. We demonstrate that B-cell depletion results in a decline in autologous neutralizing antibody (NAb) responses and a 1.7 log10 rise in HIV-1 plasma viral load (pVL). The recovery of NAbs results in a decline in pVL. The HIV-1 sequences diversify and NAb-resistant mutants are subsequently selected. These data suggest that B-cell function can contribute to the long-term control of pVL, and that NAbs may be more important in controlling chronic HIV-1 infection than previously suspected.